Women in American prisons: sex, social life, and families - Fleisher, Mark S. (Rowman & Littlefield, 2020)
"A fascinating look at the social life of women in prison. Intended to shine the light on prison social life in the face of allegations of all sorts of misconduct, deviant behaviors, and allegations"--